The mechanical properties of eggshell concrete using quarry rock dust as sand substitute - Lim, Yong Zhao (2017)
become scarce and expensive. Therefore, the replacement for fine aggregate in concrete production is required and quarry rock dust which has the physical and chemical properties almost similar to the natural sand could be the alternative. This study mainly focus on the mechanical properties of eggshell concrete with quarry rock dust compare to normal eggshell concrete. Besides that, the optimum percentage of quarry rock dust replacement will be determined to maximize the usage of by-product from quarrying activity. The test for slump, compressive strength, flexural strength and splitting tensile strength will be conducted with different percentage of quarry dust content (0%, 25%, 50%, 75% and 100%) at the curing age of 7, 14 and 28 day. The result showed that conventional eggshell concrete has better compressive strength up to 13.8% and flexural strength up to 43.95% compare to eggshell concrete with the presence of quarry rock dust. However, the eggshell concrete with quarry rock dust content perform better splitting tensile strength up to 22.08% compare to normal eggshell concrete. The flaky and dusty nature of quarry rock dust weaker the bonding of hydrated cement paste and lower the compressive and flexural strength of the concrete. The angular shape of quarry rock dust provides better interlocking ability and exhibit higher splitting tensile strength. These explained the variation in mechanical properties of quarry dust eggshell concrete compare to normal eggshell concrete. It is found that the quarry rock dust is suitable to replace fine aggregate in eggshell concrete production.